Modern English Legal Terms in Economic Discourse: Derivational Processes Analysis (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
The article deals with derivational models analysis of legal terms which function in economic discourse. The work focuses on word formation mechanisms in the system of legal terms.
Keywords: legal terms; derivational processes; derivational models; morphemic structure; economic discourse